2013
DOI: 10.1038/bmt.2013.54
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immunotherapy for plasma cell myeloma

Abstract: Allogeneic hematopoietic cell transplantation for plasma cell myeloma can lead to graft-vs-myeloma immunity and long-term survivorship, but limited efficacy and associated toxicities have prevented its widespread use. Cellular immunotherapies seek to induce more specific, reliable and potent antimyeloma immune responses with less treatment-related risk than is possible with allogeneic transplantation. Strategies under development include infusion of vaccine-primed and ex vivo expanded/costimulated autologous T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 89 publications
(96 reference statements)
0
7
0
1
Order By: Relevance
“…We and others showed that myeloma patients have high levels of circulating Tregs in their blood (Rosenblatt et al, 2013;Han et al, 2008;Garfall et al, 2013). Others have shown that high Tregs levels predict for early progression and poor outcome (Prabhala et al, 2006;Feyler et al, 2009;Braga et al, 2012;Giannopoulos et al, 2012;Muthu Raja et al, 2012;Rutella and Locatelli, 2012).…”
Section: Summary and Future Directionsmentioning
confidence: 92%
See 1 more Smart Citation
“…We and others showed that myeloma patients have high levels of circulating Tregs in their blood (Rosenblatt et al, 2013;Han et al, 2008;Garfall et al, 2013). Others have shown that high Tregs levels predict for early progression and poor outcome (Prabhala et al, 2006;Feyler et al, 2009;Braga et al, 2012;Giannopoulos et al, 2012;Muthu Raja et al, 2012;Rutella and Locatelli, 2012).…”
Section: Summary and Future Directionsmentioning
confidence: 92%
“…Allo-SCT has been shown to produce durable responses in MM patients who received grafts from HLA-matched sibling donors (Gahrton et al, 1991). It is, however, notorious for higher treatment-related toxicity, especially with myeloablative conditioning regimens which have been supplanted by reduced-intensity conditioning (RIC) regimens (Garfall et al, 2013). Despite the development of the latter, allo-SCT is still not routinely employed due to lack of survival advantage over standard ASCT (Lokhorst et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Strategies under development include infusion of vaccineprimed and ex vivo expanded/costimulated autologous T cells after high-dose melphalan, genetic engineering of autologous T cells with receptors for myeloma-specific epitopes, administration of DC/plasma cell fusions and administration expanded marrow-infiltrating lymphocytes. In addition, novel immunomodulatory drugs may synergize with cellular immunotherapies [121].…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…A potentially promising approach of obtaining myeloma-specific T cells for ex vivo manipulation and adoptive transfer involves the use of bone marrowinfiltrating cells (MILs). 46 These cells are thought to represent a polyclonal population of T cells reactive to myeloma-associated antigens but subject to tumorinduced anergy in the bone marrow microenvironment. In preclinical studies, bone marrow-derived lymphocytes have been shown to demonstrate greater proliferative response to ex vivo activation and expansion and greater myeloma-specific cytotoxicity compared with lymphocytes isolated from the peripheral blood.…”
Section: Adoptive T-cell Therapymentioning
confidence: 99%